2020
DOI: 10.7717/peerj.10382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of lenvatinib in patients with unresectable hepatocellular carcinoma who received sorafenib

Abstract: Background Lenvatinib has been approved for use in the systemic treatment for unresectable hepatocellular carcinoma (HCC). This study aimed to investigate the efficacy and safety of lenvatinib in patients with unresectable HCC who received sorafenib. Methods A total of 40 patients who received lenvatinib after sorafenib were retrospectively identified: as second line in 20 patients, third line in 10 patients, and fourth line and later lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
2
9
2
Order By: Relevance
“…Lenvatinib was started at a targeted dose of 10 mg once daily for each patient; all patients had a body weight ≥ 60 kg, whether they were part of the LT group or the control group [ 22 , 25 ]. Patients visited the outpatient clinic every 2–4 weeks for assessment of AEs, hematological and biochemical tests, AFP, vital signs, physical examination, and body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lenvatinib was started at a targeted dose of 10 mg once daily for each patient; all patients had a body weight ≥ 60 kg, whether they were part of the LT group or the control group [ 22 , 25 ]. Patients visited the outpatient clinic every 2–4 weeks for assessment of AEs, hematological and biochemical tests, AFP, vital signs, physical examination, and body weight.…”
Section: Methodsmentioning
confidence: 99%
“…The SELECT trial, which focused on lenvatinib in patients with radioiodine-refractory thyroid cancer, showed no significant difference in survival between patients who experienced prior sorafenib treatment and those who did not [ 24 ]. We also published a cohort study to investigate the efficacy and safety of lenvatinib in patients with HCC who received sorafenib [ 25 ]. The ORR was 27.5%; the median PFS and OS were 3.3 months and 9.9 months, respectively, which was non-inferior to the second-line treatment of HCC, such as ramucirumab or regorafenib [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the efficacy and safety of sorafenib and lenvatinib in patients with HCC [ 30 , 31 , 32 , 33 , 34 , 35 ]. Nevertheless, information on atezolizumab plus bevacizumab in real-world practice is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al enrolled 40 patients who received lenvatinib after sorafenib. The median overall survival (OS) was 9.8 months, and the objective response rate was 27.5%; moreover, the clinical outcomes of lenvatinib treatment in later lines were similar [ 15 ]. However, a report by Tomonari et al indicated that the objective response rate was 33.3% in the second line, and 20.0% in the third line.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lenvatinib has been approved as a first-line systemic treatment for unresectable advanced HCC. Further, some evidence indicates that lenvatinib may be used as a second-line treatment for patients who are intolerant to sorafenib or following sorafenib failure [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%